Hubungan Terpaan Media SosialInstagram @exploreBali Dengan Niat Berwisata Followers @exploreBali ke Bali - Christy, Bella; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 1 (2018), 2018)
ABSTRACT In this era of increasingly sophisticated technology, humans no longer spread information only through printed media. But also through the internet media. One of them is social media like @exploreBali, an Instagram account that inform Bali’s tourist destinations. The purpose of this study was to determine the correlation between exposure of @exploreBali social media Instagram with the intention of @exploreBali’s Instagram followers to visit Bali. This research uses quantitative method. Sampling technique used in this research is non-probability sampling and the method is purposive samplng. Data were obtained by distributing questionnaires. The results showed that there is a correlation between exposure of @exploreBali social media Instagram with the intention of @explorebali followers to visit Bali. The direction of correlation between the variables of @exploreBali Social Media Instagram with @exploreBali followers intention to travel to Bali is known to be positive and unidirectional. Which means the more frequent @exploreBali’s followers is exposed to @exploreBali social media Instagramthen the intention of @exploreBali’s followers to travel to Bali will be higher. On the other hand, this research shows only the conviction indicator is high, while the purchase indicator is relatively low. Keywords: Social Media Exposure, Instagram, @exploreBali, Travel Intentions. Correlations